Race vs politics in Guyana : political cleavages and political mobilisation in the 1968 general election - Greene, J. E. (ISER KingstonJM, 1974)
Deals with the 1968 general election in Guyana. Argues that while racial cleavage within the society is the single most important determinant of political behaviour, party organisation provides the motive force behind 'the people's choice'.